An unusual clinical vignette of oro-pharyngeal discomfort: Pterygoid Hamulus syndrome - Firdouse, Ayasha; Firdoose, Nyer; Ghousia, S (Medicine and Pharmacy Reports, 2020)
Background. A straightforward clinical reasoning is always difficult in patients with persistent orofacial pain with vague symptoms. Craniofacial pain or orofacial pain can have a mixture of causes ranging from neurogenic, myogenic, and psychogenic factors intertwined amidst the intricate anatomy with a high vascular network. This plethora of uncertainty blurs the judgment for such patients to whom we provide care. We hereby present a case of a 17 year old female with vague pain on talking, chewing and even swallowing when initially examined; this chronic orofacial pain often worsened her quality of life. The aim of this manuscript is to present a case of Pterygoid Hamulus syndrome that was misdiagnosed as glossopharyngeal and myofascial neuralgia. Methods. The condition was managed by surgical excision of the elongated pterygoid hamulus, following a recurrence of her symptoms. Results. The patient was relieved of pain only after the surgical excision of the elongated hamulus. Conclusions. The surgery was decided upon only after conservative management had not provided much relief and the manuscript also discusses the ambiguous composite pain referral pattern in Pterygoid Hamulus syndrome.